EWOM RESEARCH DYNAMICS: A BIBLIOMETRIC ANALYSIS 2020-2025 - Riyan Falah Al Wahid; Retno Widowati (RADJA PUBLIKA, 2025)
This bibliometric study analyzed the research dynamics of electronic word-of-mouth (eWOM) during the 2020–2025 period using data sourced from Scopus. The analysis revealed that Asia dominates publication contributions with 209 documents, where China, India, Indonesia, and Malaysia were identified as the main contributors. The pattern of international collaboration showed concentration around regional hubs such as the United States, China, and Indonesia, while cross-continental collaboration remained relatively limited. In terms of disciplines, business, management, and accounting remained the most dominant field (33.6%), yet there was a significant increase in contributions from environmental science and decision sciences, reflecting a shift in eWOM research themes toward issues of sustainability and environmental responsibility. The journal Sustainability Switzerland was identified as the most productive publication outlet, indicating the integration of eWOM themes within the discourse of sustainable development. This study not only updates the mapping of eWOM research post-2018 but also unveils the evolution of more interdisciplinary and sustainability-oriented themes that have not been identified in previous bibliometric studies